An unusual complication of unsafe abortion - Sunita Gupta; Himanshu Chauhan; Garima Goel; Shashank Mishra (Wolters Kluwer Medknow Publications, 2011)
Unsafe abortion is a significant medical and social problem worldwide. In developing countries, most of the unsafe abortions are performed by untrained personnel leading to high mortality and morbidity. Case Report: A 30 year-old female, gravida 7, para 6 underwent uterine evacuation for heavy bleeding per vaginum following intake of abortifacient to abort a 14 weeks gestation. The procedure was performed at a rural setup and her bowel was pulled out of the introitus through the perforated wound, an unusual complication of unsafe abortion. Illiteracy, unawareness about health services, and easy accessibility to untrained abortion providers lead to very high mortality and morbidity in India. There is unmet need to bring awareness among the people about the safe and effective methods of contraception and abortion services to avoid such complications.